2004
DOI: 10.1093/tropej/50.1.20
|View full text |Cite
|
Sign up to set email alerts
|

Lung Function and Nutritional Status of Semi-nomadic Fulani Children and Adolescents in Northern Nigeria

Abstract: The Fulani are semi-nomadic pastoralists of the western Sahel whose culture and economy are centered on cattle. We have shown previously that Fulani children and adolescents (5-18 years old) are stunted and underweight. Nutritional status and lung function were studied in Fulani children and adolescents (n = 70), aged 6-18, and compared with a non-Fulani, rural Nigerian control group (n = 153) of the same age. Participants were restricted to healthy individuals with no prior history of respiratory disease and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 0 publications
2
7
0
Order By: Relevance
“…The trend of these changes suggests dire consequences for child nutrition and health as malnutrition arising from both change in food habits and possible inequitable distribution of food within families, although yet undocumented, become rife. Studies on settled pastoral Fulani groups are scanty [ 5 ], while the increasing evidence of ill-health, morbidity and mortality in this group calls for the need to provide them with modern health care services [ 6 , 7 ]. Although the pastoral Fulani's are responsible for the provision of animal meats in countries where they are found, their welfare have been largely ignored by government due to inadequate resources since these groups are primarily nomadic.…”
Section: Resultsmentioning
confidence: 99%
“…The trend of these changes suggests dire consequences for child nutrition and health as malnutrition arising from both change in food habits and possible inequitable distribution of food within families, although yet undocumented, become rife. Studies on settled pastoral Fulani groups are scanty [ 5 ], while the increasing evidence of ill-health, morbidity and mortality in this group calls for the need to provide them with modern health care services [ 6 , 7 ]. Although the pastoral Fulani's are responsible for the provision of animal meats in countries where they are found, their welfare have been largely ignored by government due to inadequate resources since these groups are primarily nomadic.…”
Section: Resultsmentioning
confidence: 99%
“…This study observed a high level of malnutrition of 38.7% among settled nomadic Fulani children in Southwest Nigeria. Malnutrition in semi-nomadic Fulani children reported from the Northern part of Nigeria suggests that malnutrition is an important health problem among this group [7,9,12].…”
Section: Discussionmentioning
confidence: 99%
“…Measurements were performed according to standard procedures of the World Health Organization [8]. Children were weighed wearing light clothes only, and they were measured using a digital scale accurate to 0.5 kg and height was measured to within 0.25 cm using a portable Stadiometer [9]. Ages of children were obtained from their parents or caregivers or sometimes calculated using local events, which could be dated, and linked to important life history episodes.…”
Section: Study Areamentioning
confidence: 99%
“…The immigrant children have been identified as having an array of poor health status and these include: growth retardation (Geltman, Radin, Zhang, Cochran, & Meyers, 2001;Huang, Stella et al, 2006) obesity (Fredriks, Buuren, Jeurissen, et al, 2004;Geltman, Radin, Zhang, Cochran, Meyers, 2001;Guarnaccia, Lopez, 1998), and mental health problems (Guarnaccia, Lopez, 1998;Hu, 2004). For children of internal migration, some studies have showed that they were stunted and underweight due to their bad lifestyles (Glew, Brock et al, 2004;Slesinger, Christenson, Cautley, 1986). Slesinger reported that the migrant farmers' children are at substantially greater risk of health problems and earlier mortality than the urban children in Wisconsin, since they lack access to regular physical checkup (Slesinger, Christenson, Cautley, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Slesinger reported that the migrant farmers' children are at substantially greater risk of health problems and earlier mortality than the urban children in Wisconsin, since they lack access to regular physical checkup (Slesinger, Christenson, Cautley, 1986). Glew showed that west Africa Fulani immigrant children and adolescents (5 -18 years old) have smaller physiques than Nigerian children in northern Nigeria due to their poor lifestyles (Glew, Brock, et al, 2004). However, some studies have shown that immigration are likely to have earlier onset of puberty ,improved physical status and reduction of the prevalence of stunting (Bogin, Smith et al, 2002;Garnier, Ndiaye, Benefice, 2003).…”
Section: Introductionmentioning
confidence: 99%